Design and Usability Evaluation of Communication Board for Deaf People with User-Centered Design Approach - Dermawi, Rizdania; Tolle, Herman; Aknuranda, Ismiarta (International Journal of Interactive Mobile Technologies (iJIM), 2018)
People interact their environment by communicating, but some limitation may exist such as hearing disability that occurs to deaf people. Usually, they communicate by using sign language. Unfortunately, there is various sign language in the world. This research is evaluating the usability of smartphone for communication board that can be used by deaf people to communicate to others, especially the people who don’t understand the sign language. Usability testing is to measure the user performance for mobile applications. The five criteria for the usability, according to Nielsen are learnability, efficiency, memorability, errors, and satisfaction. The study obtained the result of 88.36% of usability testing.